Changing Teacher’s Teaching Behavior to Improve Classroom Teaching Effectiveness Through ODI（Organization Development Interventions） An Action Research at College of International Business (CIB), in Zhejiang Yuexiu University of Foreign Languages (ZYUFL), in China - Manying, Wang (ABAC ODI JOURNAL Vision. Action. Outcome, 2021)
Based on the analysis and intervention of CIB in ZYUFL teachers’ teaching behavior, this paper aims to improve the classroom teaching effectiveness, including teachers’ teaching outcome and students’ learning outcome. First, it designed an interview outline for the research topic with business schoolteacher before the formal formulation of the intervention program. Second, we have consulted the contents about the effect of classroom teaching in colleges and universities at home and abroad, and fully understood the importance of improving the quality of classroom teaching. Third, the paper reviews about the main variables such as teacher’s teaching behavior and teaching effectiveness. It puts forward the theoretical framework, conceptual frame of this study work and action research framework. It uses 360-degree evaluation method to evaluate teachers’ teaching behavior and teaching effectiveness. Fourth, the intervention program aimed at changing teachers’ teaching attitude, teaching content and teaching methods is designed, and the concrete method of data collection is formulated. Fifth, through ODI for 7 months, the data has been collected before and after the intervention. It uses EXCEL and SPSS to compare and analyze the data. Through mean analysis, teachers’ teaching behavior and teaching effectiveness have been significantly improved. Through paired sample analysis with the control group, the change of teachers’ teaching behavior is significant, but the evaluation gap of teaching effectiveness, especially the students’ learning outcome is not obvious. Finally, the relevant research is prospected and suggested, and the short comings of this research are pointed out.